Coherent terahertz emission from free-electron-driven Fabry–Pérot resonators with coupled grooves. (11th November 2020) - Liu, Weihao; Zhang, Liwen; Yu, Zijia; Liu, Yucheng; Li, Weiwei; Jia, Qika; Sun, Baogen; Xu, Hongliang; Liu, Wenxin
Abstract: Fabry–Pérot (FP) resonators with metallic subwavelength grooves or holes, which have been extensively applied in optical region, have recently attracted increasing interest for terahertz wave generation and manipulation. However, the practices of such resonators in the terahertz region are greatly restricted by the low energy-capacity and by the difficulty of manufacturing high-aspect-ratio grooves/holes. Here we illustrate a kind of terahertz FP resonator formed by a cluster of coupled grooves with low-aspect-ratio, which has much higher energy-capacity, higher quality-factor and is much easier to fabricate than one formed by a single uncoupled-groove. Using free-electron beams to excite an array of such FP resonators, coherent terahertz emission can be achieved, the intensity of which is more than an order of magnitude higher than that from an array of uncoupled-grooves, affording a promising way for high-power and coherent terahertz wave generation.